COMPARATIVE ANALYSIS OF LEBANON DEVELOPMENT. PROSPECTS FOR COOPERATION WITH THE RUSSIAN FEDERATION - M.A.E. El Moussawi; Zh. V. Mironenkova; S. Z. Umarov; O. I. Knysh; O. D. Nemyatykh (Фармация и фармакология (Пятигорск))
The objective of the research was to conduct a comparative analysis of the development of Lebanon based on a number of demographic, economic and social indicators characterizing the health care of Lebanon, and to determine the prospects for the cooperation with the Russian Federation (RF) in the pharmacy field.Materials and methods. The studies were conducted from 2009 to 2016. The objects were the statistical data accumulated on the basis of the data from national institutions and international organizations. These data were published annually in the reports of the Department of Economic and Social Affairs, the United Nations Population Division for 11 countries in the Middle East: Bahrain, Jordan, Yemen, Kuwait, Lebanon, United Arab Emirates, Oman, Saudi Arabia (Asian countries); Egypt, Sudan, Tunisia (North African countries). The research methods were: a comparative analysis, analytical grouping of data, ranking.Results. A comparative analysis of demographic, economic and social indicators revealed that low mortality rates and high life expectancy in Lebanon were achieved both due to a satisfactory level of health care financing (Rank 5) and due to the adoption of adequate decisions in organizing and managing the Lebanese health care system. The positive trends that were inherent in the Lebanese health care system in previous decades continued to operate within the framework of earlier inertia, while migration flows intensified. However, there has been a slowdown in the decline in infant mortality in the dynamics of growth rates, which is a signal of the emergence of negative processes in the social sphere of the country.Conclusion. The current situation in the Lebanese health care system, associated with limited financial resources, poses new challenges in the search for managerial decisions in the field of organizational management. The import of drugs from the Russian Federation will provide a significant reduction in the financial costs of providing the population of Lebanon and migrants with medicines which will increase the monetary costs of providing medical care.